Studi Bakteri Pendegradasi Fenol pada Lapisan Acrotelm dan Catotelm Di Hutan Rawa Gambut - Handayani, Wiji Pamungkas; Anshari, Gusti Zakaria; Indrawati, Urai Suci Yulies Vitri (Pedontropika: Jurnal Ilmu Tanah dan Sumber Daya Lahan, 2023)
Peat soils are formed from woody materials which generally contain a lot of lignocellulosic organic  compounds such as lignin which in the degradation process produces reactive carboxyl groups and  phenolic  compounds.  Degradation  of  phenolic  compounds  can  be  carried  out  enzymatically  by  phenol-  degrading bacteria. The purpose  of this study was to compare the number  of  bacterial colonies  degrading phenolic compounds in the acrotelic and catotelm layers in the upstream and downstream  locations of the peat swamp forest in Permata Village, Terentang District, Kubu Raya Regency. Soil  samples were taken in 2 plots (upstream and downstream from the canal blocking) at a distance of 500  meters using a peat drill. Each plot was then taken 3 drill points to form a triangular pattern with a  distance of 30 meters with a peat depth level (Acrotelm) 0-10 cm, 10-20 cm and peat depth (Catotelm)  300-310 cm, 310-320 cm. Bacterial colonies were counted using the Total Plate Count method on  Mineral Salt Medium and pure phenol selective media. Total phenolic compounds in peatlands were  tested using 10% Folin-Ciocalteu solution and 2% Na2CO3. The number of bacterial colonies at  locations  upstream  from  the  canal  blocking  in  the  acrotelmic  layer  is  0-10  cm  deep  (7,5x104  cfu/gr)  and  10-20 cm deep (8,8x104  cfu/g), while bacteria in the catotelm layer are 300-310 cm deep (2,1x104  cfu/gr)  and  a  depth  of  310-320  cm  (2,2x104  cfu/gr).  The  number  of  bacterial  colonies  downstream  from  the canal blocking in the acrotelm layer at a depth of 0-10 cm (2,3x104  cfu/gr) and at a depth of 10-20  cm (3,1x104  cfu/gr), while bacteria in the catotelm layer at a depth of 300-310 (1,7x104  cfu/g) and a  depth  of  310-320 cm  (1,6x104  cfu/g).